Lipid droplet biogenesis from specialized ER subdomains - Vineet Choudhary; Roger Schneiter (Microbial Cell)
Lipid droplets (LDs) are cellular compartments dedicated to the storage of metabolic energy in the form of neutral lipids, commonly known as “fat”. The biogenesis of LDs takes place in the endoplasmic reticulum (ER), but its spatial and temporal organization is poorly understood. How exactly sites of LD formation are selected and the succession of proteins and lipids needed to mediate this process remains to be defined. In our current study we show that the yeast triacylglycerol (TAG)-synthases, Lro1 and Dga1 get recruited to discrete ER subdomains where they initiate TAG synthesis and hence LD formation (Choudhary et al. (2020), J Cell Biol). These ER subdomains are defined by yeast seipin, Fld1, and a regulator of diacylglycerol (DAG) production, Nem1. Both Fld1 and Nem1 are ER proteins which localize at contact sites between the ER and LDs. Interestingly, even in cells lacking LDs, Fld1 and Nem1 show punctate localization at ER subdomains independently of each other, but they are required together to recruit the TAG-synthases and hence create functional sites of LD biogenesis. Fld1/Nem1-containing ER subdomains recruit additional LD biogenesis factors, such as Yft2, Pex30, Pet10 and Erg6, and these membrane domains become enriched in DAG. In conclusion, Fld1 and Nem1 play a crucial role in defining ER subdomains for the recruitment of proteins and lipids needed to initiate LD biogenesis.